2007
DOI: 10.1002/j.2161-0045.2007.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Career Counseling With African Immigrant College Students: Theoretical Approaches and Implications for Practice

Abstract: The purpose of this article is twofold: (a) to explore the career development needs and issues that are unique to Black sub‐Saharan African immigrants, with an emphasis on college students, and (b) to discuss how career development professionals can implement strategies to better serve these students. The number of Black immigrants from sub‐Saharan African countries has increased recently. Many immigrants are confronted with complex life decisions. Career counselors are in a unique position to assist. Theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 83 publications
1
61
0
Order By: Relevance
“…Stebleton's (2007) work corroborates this finding. He found out that adolescents possessed external locus of control and thinks that there are different outside elements that are capable of influencing their career decision.…”
Section: Discussion Of Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…Stebleton's (2007) work corroborates this finding. He found out that adolescents possessed external locus of control and thinks that there are different outside elements that are capable of influencing their career decision.…”
Section: Discussion Of Findingssupporting
confidence: 77%
“…Some have shown positive correlation between locus of control and work fatigue while a study by Ghahramani, Arastehnazar and Meenar (2011) found no correlation between the two. Stebleton (2007) discovered that adolescents possessed external locus of control and thinks that there are different outside elements that are capable of influencing their career decision. Moreover, Muner and Morre (2003) have associated internal locus of control with high self esteem, job satisfaction, high self efficacy and high education aspirations.…”
Section: Introductionmentioning
confidence: 99%
“…As the overall immigration rates and enrollments increase in the United States, the experiences of immigrant student in college require attention, especially in terms of student development, engagement, and persistence (Conway, 2009(Conway, , 2010Kim, 2009;Stebleton, 2007). Immigrant students are often the first in their families to attend college, and according to Choy (2002), first-generation students are more likely than their more advantaged peers to be students of color, older than 24 years, female, nonnative speakers of English, and born outside the United States.…”
Section: Exploring Immigrant Students' Experiencesmentioning
confidence: 99%
“…Based on the findings of this study, these assessment tools or strategies seem most beneficial when individuals need to re-author new stories that reflect their preferred ways of existing and navigating a new environment or society (Stebleton, 2007). These strategies may also encourage immigrants to talk about their own stories (Savickas, 2005;Stebleton, 2007), including, issues relating the loss occupational status, acculturation, and negotiating multiple identities.…”
Section: Implications For Practicementioning
confidence: 96%
“…Engaging in career planning may be perceived as unimportant relative the needs of immigrants' personal adjustment social integration. For example, Stebleton (2007) contends that traditional decision-making models based on Western models that promote long-range career planning may not be useful for African students because of complex decisions, such as balancing work-life concerns and multiple identities. Hence, African students tend not to take a planful approach to career planning because of the external factors that dictate their future (Stebleton).…”
Section: Career Development Research In Human Resource Developmentmentioning
confidence: 99%